Reduced state transition barrier of CDK6 from open to closed state induced by Thr177 phosphorylation and its implication in binding modes of inhibitors - He, Huan; Xu, Juan; Xie, Wen; Guo, Qing-Lian; Jiang, Feng-Lei; Liu, Yi (Biochimica et biophysica acta, 2018)
CDK6 is considered as a highly validated anticancer drug target due to its essential role in regulating cell cycle progression at G1 restriction point. Activation of CDK6 requires the phosphorylation of Thr177 on A-loop, but the structural insights of the activation mechanism remain unclear. Herein, all-atoms molecular dynamics (MD) simulations were used to study the effects of Thr177 phosphorylation on the dynamic structure of CDK6-Vcyclin complex. MD results indicated that the free energy barrier of the transition from open to closed state decreased ~47.2% after Thr177 phosphorylation. Key steps along the state transition process were obtained from a cluster analysis. Binding preference of ten different inhibitors to open or closed state were also investigated through molecular docking along with MD simulations methods. Our results indicated that Thr177 phosphorylation increased the flexibility around the ATP-binding pocket. The transition of the ATP-binding pocket between open and closed states should be considered for understanding the binding of CDK6 inhibitors. This work could deepen the understanding of CDKs activation mechanism, and provide useful information for the discovery of new CDKs inhibitors with high affinity and specificity. Phosphorylation of Thr177 could activate CDK6 by lowering its state transition barrier form open to closed state, while the binding preferences of three types of CDK6 inhibitors vary. [Display omitted] •The free energy barrier of CDK6-Vcyclin between open and closed states decreased ~ 47.2% after Thr177 phosphorylation.•Key steps along the state transition processes are proposed.•Binding preference of ten inhibitors to open or closed states are investigated by docking and MD simulations methods.•Good linearity between the calculated binding free energies and experimental measurements for inhibitor affinity.